10 most important contemporary challenges in the management of SLE. Issue 1 (10th January 2019) - Felten, Renaud; Sagez, Flora; Gavand, Pierre-Edouard; Martin, Thierry; Korganow, Anne-Sophie; Sordet, Christelle; Javier, Rose-Marie; Soulas-Sprauel, Pauline; Rivière, Marianne; Scher, Florence; Poindron, Vincent; Guffroy, Aurélien; et al.
Abstract : From a 1-year survival of less than 50% before the discovery of glucocorticoids to over 90% at 10 years in most dedicated centres, the spectrum of SLE has profoundly evolved. Despite this improvement, several major challenges currently remain. The aim of this review is to analyse what are, according to us, the 10 most important contemporary challenges in the management of SLE. Among those are the need to treat to target to favour disease remission (or low disease activity), limit the use of glucocorticoids, derive more comprehensive tools for the evaluation of disease activity, develop more effective drugs (yielding successful trials), dissect the heterogeneity of the disease both at the molecular and genetic levels, identify relevant biomarkers for individualised treatment, manage fertility and pregnancy, tackle comorbidities such as cardiovascular risk, the prevention of infections and osteoporosis, improve the network of care (from the patients' perspective), and favour a holistic approach (integrating fatigue, adherence to treatment, physical activity). Altogether, these 10 contemporary challenges in SLE may be considered as a roadmap for those involved in the daily care of patients with SLE, as well as for researchers who may wish to contribute to an improved management of this rare and complex disease.